Study of the behavior of damaged low-velocity impact carbon/epoxy/AL2024-T3 hybrid laminates - Fatima Zohra Daouache; Amin Houari; Mourad Lounis; Lecheb Samir; Salah Amroune; Kouider Madani; Barhm Mohamad; Mohamed Belhouari (Discover Materials)
Abstract Aluminium and layered composite structures currently play a crucial role in the aviation sector. These structures may be susceptible to inadvertent impacts from several sources. Low-velocity impact is a type of unintended aggression that causes severe harm to composite materials and can greatly diminish their residual resistance. This research presents a novel stack of unconventional hybrid laminates aimed at improving both stiffness and elasticity through a multi-material design. We focus on analyzing the main factors responsible for impact damage in hybrid structure. Tie contact were used between plies of the composite plate in all models. Using the HASHIN criterion, we analyze the impact velocity, impact sequence, composite thickness, impact energy level, impact efforts, and damaged zones in the composite, matrices, and fibers. The primary results indicate that both impact energy and composite thickness have a substantial influence on the energy absorbed by the composite and the impact exerted in the affected area.